A protection motivation theory-guided telehealth coaching program for middle-aged adults with cardiometabolic risk: A feasibility trial - Zoe Ching-man Kwok; Hon-lon Tam; Benny Chung-ying Zee; Sally Wai-sze Lo; Fiona Wing-ki Tang; An Tao; Helen Yue-lai Chan (BMC Public Health)
Abstract Background Health coaching to address the escalated cardiometabolic risk in middle-aged adults in primary health care is underexplored. This study aimed to examine the feasibility and acceptability of a protection motivation theory-guided telehealth coaching program among middle-aged adults with cardiometabolic risks. Methods This was a pretest–posttest study. The three-month intervention included four nurse-facilitated telehealth sessions tailored to individual cardiometabolic risks. Results Thirty participants were recruited through social media and a community center. The eligibility and enrollment rates were 16.1% and 78.9%, respectively. Attrition at six months after enrollment was 33.3%, and intervention attendance was 82.5%. Most of the participants (76.7%) were satisfied with the program. Significant improvements were noted in the INTERHEART score for cardiometabolic risks, self-efficacy, anxiety, stress, and central obesity but not in health-promoting behaviors, depression, sleep quality, physical activity level, and physiological outcomes at six-month post-enrolment. Conclusion A theory-based telehealth coaching was feasible and well-accepted among middle-aged adults, with potential in reducing cardiometabolic risks among middle-aged adults in primary care. This study revealed significant improvement in cardiometabolic risk, self-efficacy, anxiety, stress, and central obesity but changes for health-promoting behaviors, depression, sleep quality, physical activity level, and physiological outcomes were not noted. Progression to a definitive trial was supported with implication for future trials, including lowering the threshold of cardiometabolic risk to improve subject recruitment, change of assessment sessions to promote adherence to fasting instruction, and use of digital recording to facilitate health coaching process. Trial registration : This trial was retrospectively registered on 05/07/2022 at ClinicalTrials.gov (identifier: NCT05444140).